Drosophila Vps13 Is Required for Protein Homeostasis in the Brain - Vonk, JJ; Yeshaw, WM; Pinto, F; Faber, AI; Lahaye, LL; Kanon, B; van der Zwaag, M; Velayos-Baeza, A; Freire, R; van IJzendoorn, SC; Grzeschik, NA; Sibon, OC (Public Library of Science, 2017)
Chorea-Acanthocytosis is a rare, neurodegenerative disorder characterized by progressive loss of locomotor and cognitive function. It is caused by loss of function mutations in the Vacuolar Protein Sorting 13A (VPS13A) gene, which is conserved from yeast to human. The consequences of VPS13A dysfunction in the nervous system are still largely unspecified. In order to study the consequences of VPS13A protein dysfunction in the ageing central nervous system we characterized a Drosophila melanogaster Vps13 mutant line. The Drosophila Vps13 gene encoded a protein of similar size as human VPS13A. Our data suggest that Vps13 is a peripheral membrane protein located to endosomal membranes and enriched in the fly head. Vps13 mutant flies showed a shortened life span and age associated neurodegeneration. Vps13 mutant flies were sensitive to proteotoxic stress and accumulated ubiquitylated proteins. Levels of Ref(2)P, the Drosophila orthologue of p62, were increased and protein aggregates accumulated in the central nervous system. Overexpression of the human Vps13A protein in the mutant flies partly rescued apparent phenotypes. This suggests a functional conservation of human VPS13A and Drosophila Vps13. Our results demonstrate that Vps13 is essential to maintain protein homeostasis in the larval and adult Drosophila brain. Drosophila Vps13 mutants are suitable to investigate the function of Vps13 in the brain, to identify genetic enhancers and suppressors and to screen for potential therapeutic targets for Chorea-Acanthocytosis.